Problem Based Learning with a Scientific Approach with Character in Mathematics Learning - Wakit, Ahmat; Kusumodestoni, R. Hadapiningradja (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
The studied aims to determined the characteristics of the development of learned devices with the problem-based learned model with a scientific approached which container the character in math subject. The research method used is a development research. Development is carried out with the preparation of valid, practical and effective tools. The learned tools developed were syllabus, (RPP) Learning Implementation Plans, (LKS) Student Worksheets, Student Books, and TKPM (Problem Solving Ability Tests). After the learned device valid then tested, the experiment was carried out by observed the learned process, process skills, students' character, at the end of the learned process did by TKPM and filled in the student response questionnaire. Data were analyzed to determined the practicality and effectiveness of the used of learned devices. The results showed: (1) the average score of the learned device validation results was 4.37 in the very good category so the devices developed were valid; (2) the application of practical learned tools because the average score of the teacher's ability to manage to learned is 3.98 in the good category and the average score of 4.36 student respons is in the very good category; (3) the application of effective learned devices because TKPM has achieved classical completed, the average TKPM experimental class better than the control class, the proportion of completed TKPM students experiment better than control class students, there is a positive influence was students' process and attitude skills towards TKPM, there is an increase in mathematical problem-solved abilities.